A New Assessment of Activities of Daily Living for Thai Stroke Patients - Sopida Apichai (Chiang Mai University, 2020)
Chiang Mai University (CMU) Journal of Natural Sciences is dedicated to the publication of original research in Sciences & Technology and the Health Sciences. Submissions are welcomed from CMU, as well as other Thai and foreign institutions. All submissions must be original research not previously published or simultaneously submitted for publication. Manuscripts are peer reviewed using the double -blinded review system by at least 2 reviewers before acceptance. The CMU Journal of Natural Sciences is published four times a year, in January, April, July and October.